Patient-Generated Subjective Global Assessment and Nutritional Risk Indicators in Oncology Patients Receiving Chemotherapy - Gomes, Nayara de Souza (2015)
Introduction: The Subjective Global Assessment produced by the patient is recommended for during the nutritional care in oncology, for the early detection of nutritional risk or malnutrition. The location of the tumor and the chemotherapy course may, in themselves, aid in the detection of nutritional risk. Objective: To describe the classification of nutritional status according to the subjective method, together with nutritional risk factors in cancer patients undergoing chemotherapy. Method: This is a case series study held at the chemotherapy unit of a university hospital, from August to December 2014. The participants were adult and elderly outpatients of both sexes, aged ≥20 years, diagnosed with cancer, and who had begun the first cycle of chemotherapy. The location of the tumor and the antineoplastic therapy were used as indicators of nutritional risk. Nutritional assessment was performed via the Subjective Global Assessment produced by the patient themselves. Results: 30 patients were studied, with an average age of 49.1 ± 16.4 years. Twenty-five respondents (83%) were treated solely with chemotherapy. According to the location of the tumor and the course of chemotherapy, 67% and 100% of the cases, respectively, were classified as medium to high nutritional risk. By subjective assessment, 17 (56.7%) presented a nutritional risk or moderate malnutrition (Grade B) and 6 (20%) severe malnutrition (Grade C). By way of the score via subjective assessment, the need for nutritional intervention was detected in 23 cases (76.7%). Conclusion: The sample studied revealed high frequencies of tumors and aggressive therapies that could cause nutritional risk/malnutrition, highlighting the necessity of nutritional therapy.